2002
DOI: 10.1021/jp021361z
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics and Mass Transport in Wall Tube and Microjet Electrodes. Simulation and Experiment for Micrometer-Scale Electrodes

Abstract: Mass transport to micrometer-sized electrodes in a microjet (wall-tube) electrode configuration is examined experimentally and through finite element modeling. Electrochemical imaging experiments reveal that local mass transport is highly sensitive to the lateral position of the nozzle with respect to the electrode. When these two components are arranged coaxially, there is a pronounced minimum in the mass transfer rate to the electrode, as determined from transport-limited current measurements. Small lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(48 citation statements)
references
References 11 publications
0
48
0
Order By: Relevance
“…This would then mean that the formation of OH ads on polycrystalline platinum in sulphuric acid, although fast and reversible at the initial adsorption sites must undergo a relatively slow diffusion process away from that initial site. 90 There are supporting arguments in the literature for this. Davies et al 63 studied the oxidation of CO ads on ruthenium modified Pt(111) and suggested that the second peak in the CO ads oxidation transients was associated with the spill-over and diffusion of the oxidant produced at the ruthenium sites via a surface Grotthus-like mechanism.…”
Section: Transients In the Absence Of Co Adsmentioning
confidence: 90%
See 4 more Smart Citations
“…This would then mean that the formation of OH ads on polycrystalline platinum in sulphuric acid, although fast and reversible at the initial adsorption sites must undergo a relatively slow diffusion process away from that initial site. 90 There are supporting arguments in the literature for this. Davies et al 63 studied the oxidation of CO ads on ruthenium modified Pt(111) and suggested that the second peak in the CO ads oxidation transients was associated with the spill-over and diffusion of the oxidant produced at the ruthenium sites via a surface Grotthus-like mechanism.…”
Section: Transients In the Absence Of Co Adsmentioning
confidence: 90%
“…It is perhaps because of this underlying assumption that the analysis of Pt oxide growth has often been limited to potentials above 0.8 V [18][19][20][21][22][23] . In the paper by Conway et al 22 the typical two anodic peaks and shoulder in the Pt i-V profile 90 are considered as occurring before a monolayer of hydroxyl has been formed, even at a single crystal surface, and based on this assumption they showed that the hydroxyl monolayer became irreversibly adsorbed above about 0.95 V, with a coverage of approximately 0.25, which was well below the 95 monolayer limit of one hydroxyl per Pt, which occurred at 1.1 V. However, it is unlikely that the formation of an adsorbed layer of hydroxyl could be anything other than reversible unless it results in a reorganisation of the Pt surface with migration of hydroxyl into the bulk, as suggested by Conway 100 et al (see Fig. 21.…”
Section: Oxide Versus Hydroxyl Formationmentioning
confidence: 97%
See 3 more Smart Citations